2003
DOI: 10.1016/s1571-0653(04)00425-1
|View full text |Cite
|
Sign up to set email alerts
|

The Game Chromatic Index of Forests of Maximum Degree 5

Abstract: Using a refinement of the methods of Erdös et al. [6] we prove that the game chromatic index of forests of maximum node degree 5 is at most 6. This improves the previously known upper bound 7 for this parameter. The bound 6 is tight [6].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…It was shown that if ∆ = 3 or ∆ ≥ 6, then any tree T with ∆(T ) = ∆ satisfies χ ′ g (T ) ≤ ∆+1. In [1], this result was extended to trees (and forests) with ∆ = 5. The case for ∆ = 4 remains open, indicating the difficulty of determining these parameters, even in the non-relaxed environment.…”
Section: Introductionmentioning
confidence: 97%
“…It was shown that if ∆ = 3 or ∆ ≥ 6, then any tree T with ∆(T ) = ∆ satisfies χ ′ g (T ) ≤ ∆+1. In [1], this result was extended to trees (and forests) with ∆ = 5. The case for ∆ = 4 remains open, indicating the difficulty of determining these parameters, even in the non-relaxed environment.…”
Section: Introductionmentioning
confidence: 97%
“…We consider in this paper an edge-coloring game studied in [1,2,6,7,8,9]. In the game, two players, Alice and Bob, alternately select a color from a set of colors and put it on an uncolored edge of an initially uncolored, finite and simple graph G such that adjacent edges receive distinct colors.…”
Section: Introductionmentioning
confidence: 99%
“…Erdös et al [7] showed that best possible upper bound for the class of trees T with maximum degree ∆(T ) is at least ∆(T ) + 1 if ∆(T ) ≥ 2. The upper bound ∆(T ) + 1 holds when ∆(T ) = 3 [1,5] or ∆(T ) ≥ 5 [2,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper bounds for the game chromatic number have been determined for forests [6], outerplanar graphs [7], graphs embeddable in an orientable surface [11], line graphs of k-degenerate graphs [4], line graphs of forests with maximum degree ∆ = 4 [4,5,1], and planar graphs [11,15].…”
Section: Introductionmentioning
confidence: 99%